Nutritional status: changes with ageing - Santos,Ana Célia Oliveira dos (2010)
Brazil has suffered remarkable changes concerning to its age groups distribution. Elderly actually do a sum of 15 millions of people. In this reality are found various nutritional disorders within this age group. This study aims to highlight the ageing modifications, which influence the nutritional state, to establish a more updated approach on the main nutritional assessment methods and to identify the nutritional profile of Brazilian elderly population. This work was performed through a review on publications from 1987 to 2009, based on textbooks, SciELO, Lilacs e Medline data bases. Through this search work was possible to observe that nutritional disorders are even more prevalent among elderly, being obesity in a much more ascending rate. Considering the nutritional assessment methods now available, there is no golden standard that claims hegemony. One should emphasize the physiological alterations of ageing through out the whole process of nutritional evaluation in elderly people.